PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN KOPERASI DI KECAMATAN SUMBERSARI JEMBER - Riska Ayu Pramesthi (Growth, 2017)
Motivation is something that should be done by the management in improving job satisfaction and employee performance. The purpose of this study was to determine the effect of motivation and job satisfaction on employee performance cooperatives in Kecamatan Sumbersari Jember. The population data collected in the study were all accounts totaling 100 officers from 20 cooperatives that made the object of research. The sampling technique used is proportionate stratified random sampling technique which this technique is used when the population have a member who is not homogeneous and stratified proportionally, to determine the results using the Partial Least Square (PLS). The study states that motivation positive and significant effect on the performance, motivation and significant positive effect on job satisfaction, job satisfaction and a significant positive effect on performance. The implication of this study is two-factor theory also has other limitations that situational variables. Herzberg assumes the existence of a correlation between satisfaction and productivity.However, research conducted by Herzberg emphasis on satisfaction and productivity ignore. To maintain and improve the performance of cooperatives based on the perspective of motivation theory (Herzberg) which reveal individual motives for obtaining a motivator and hyegine factors need to be considered for future research. Not all topics of research problems can be implemented and tested with Herzberg's theory, because the companies and institutions have different problems.